(untitled) (The Research of Medical Science Review, 2024)
Objective: Determine the prevalence of low back pain (LBP) among motorcycle riders who come to the GMCTH OPD. Methods: This cross-sectional study was carried out among Gujranwala locals who were visiting the GMCTH OPD in Pakistan. Included were all male bikers who ride motorcycles. Data was gathered using an organized questionnaire. Data on low back pain, the most common riding posture, position changes, visits to a consultant for LBP, deviations from normal routine, decreased physical activity in the past year, decreased leisure activity due to LBP, and LBP in the previous week were gathered. Results: The mean age of the 100 participants was 22 years. 65 BIKERS, or 65%, reported having LBP. when 33 (33%) reported bending forward when riding, the majority of riders (n = 67, 67%) reported maintaining an upright posture. It was also discovered that the commonly altered location was mostly higher, i.e. (n=87, 87%). There was a significant correlation found between LBP and age (p-value 0.003), daily motorbike time (p-value 0.005), and frequency of position changes (p-value 0.003). Conclusion: In summary, low back pain is prevalent among motorcycle riders. People who ride motorcycles and experience low back discomfort were shown to have significantly greater levels of age, daily riding time, and posture changes.